LITERATURE IN LANGUAGE TEACHING - Rahayu, Mundi (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2009)
The role of literature in the ELT classroom has been re-assessed by many experts, and now many of them view literary texts as providing rich linguistic input, in addition to effective stimuli for students to express themselves in other languages. In this way, literature can be a potential source of learner motivation. Literary texts offer a rich source of linguistic input and can help learners to practice the four language skills -speaking, listening, reading and writing- in addition to exemplifying grammatical structures and presenting new vocabulary. It is found out as well that literary texts provide opportunities for multi-sensorial classroom experiences and can appeal to learners with different learning styles.